Multigenerational transmission of liability to psychiatric illness in offspring of parents with bipolar disorder. (21st June 2018) - Post, Robert M; Altshuler, Lori L; Kupka, Ralph; McElroy, Susan L; Frye, Mark A; Rowe, Michael; Grunze, Heinz; Suppes, Trisha; Keck, Paul E; Leverich, Gabriele S; Nolen, Willem A
Abstract : Introduction: Instead of the typical assessment of risk of illness in the offspring based on a parent with bipolar disorder, we explored the potential multigenerational conveyance across several disorders of the vulnerability to illness in the offspring of a patient with bipolar disorder. Methods: A total of 968 outpatients (average age 41 years) with bipolar illness gave informed consent and filled out a detailed questionnaire about a family history in their parents, grandparents, and offspring of: depression; bipolar disorder; alcohol abuse; substance abuse; suicide attempt; or "other" illness. Of those with children, 346 were from the USA and 132 were from Europe. Amount and type of illness in progenitors in two and three previous generations were related to offspring illness. Results: The type of illness seen in both prior generations was associated with the same type of illness in the offspring of a bipolar patient, including depression, bipolar disorder, alcohol and substance abuse and "other" illness, but not suicide attempts. There was an impact of multiple generations, such that depression in grandparents and/or great‐grandparents increased the risk of depression in the offspring from 12.6% to 41.4%. Conclusions: A family history of illness burden in prior generations was previously related to an earlier age of onset of bipolar illness in our adult patients with bipolar disorder and is now also found to be related to the incidence of multiple psychiatric illnesses in their offspring. Genetic and epigenetic mechanisms deserve consideration for this multigenerational conveyance of illness vulnerability, and clinical and public health attempts to prevent or slow this transmission are indicated.